Managing Cognitive Functions of Classical Dance Students: Classroom Environment and Pedagogical Conditions - Egor A. Alferov (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
Classical dancing develops cognitive functions in junior and middle class students of choreographic schools. The modern media environment forms a fragmentary type of information perception and thinking. The article discusses classroom environment and essential characteristics of classical dance acquisition. Based on the applied character of the discipline, the educational space is a set of pedagogical conditions that implement sequences of functions, from cognitive to analytical and operational, that control and correct motor actions in the learning process. The research, which relied on standard methods, included 45 students aged 9–12 from the Moscow State Academy of Choreography. Based on the theoretical analysis of classical dance teaching in the context of motor skills formation, it yielded specific recommendations on developing professional attention by means of controlling students’ cognitive functions. As a result, the classical dance teacher activates in students those perceptual functions that are necessary at a particular moment of dancing or practicing dance movements.